Mathematical Study of Temperature Distribution in Human Dermal Part during Physical Exercises - Gurung, Dil Bahadur; Shrestha, Dev Chandra (Journal of the Institute of Engineering, 2017)
The purpose of this paper is to model metabolic rate that governs the behavior exhibited by various exercises over the period. This model equation is used in one dimensional Pennes’ bio-heat equation to study the temperature distribution in dermal part of tissue layers due to various exercises. The appropriate Dirichlet and Neumann boundary conditions are used. The solution of the bio-heat equation is then obtained using FEM technique and the simulated results are presented graphically. Journal of the Institute of Engineering, 2016, 12(1): 63-76